Crystallinity in poly(vinyl alcohol) 2. Computer modelling of crystal structure over a range of tacticities - Assender, H; Windle, A (1998)
In Part 1 of this series, the behaviour of the crystalline phase in atactic poly(vinyl alcohol) was discussed. This paper examines the detail of the crystal structure by use of molecular mechanics modelling, and extends the prediction of crystal structure across the whole range of tacticity, the extremes of which have yet to be synthesised. The variation in the crystal structure with changes in tacticity is modelled in the light of experimentally observed changes in physical properties. As the extremes of stereoregularity are approached, novel crystal structures are considered and extensive comparisons made with existing X-ray diffraction data for the limited tacticity range available experimentally. A crystal structure is proposed for a recently synthesised isotactic rich polymer which was observed to have a distinctly different X-ray powder diffraction trace from the atactic material. Finally, the possibility that water may be incorporated into the atactic crystal structure is discussed and the change in the X-ray diffraction behaviour if water is included is simulated for comparison with experimental data. © 1998 Elsevier Science Ltd. All rights reserved.